Boosting Light‐Driven Photocatalytic Water Splitting of Bi4NbO8Br by Polarization Field. Issue 9 (3rd July 2022) - Xu, Ruohang; Wang, Yuqing; Cui, Dandan; Du, Kunrong; Shi, Zhijian; Zhang, Hongrun; Xu, Ze; Hao, Weichang; Du, Yi
Abstract : Photocatalysis is regarded as a promising approach to solve the energy crisis by producing H2 from water splitting reaction driven by solar light. However, low photogenerated charge carriers yielding and separating rates limit the quantum efficiency in photocatalytic reactions, which is a common drawback for most visible‐light photocatalysts. Herein, a bismuth‐based photocatalyst, Bi4 NbO8 Br, through intercalating NbO6 octahedrons into layered BiOBr nanosheets, is designed and fabricated. Bi4 NbO8 Br demonstrates an enhanced photocatalytic water splitting ability as compared to BiOBr in visible light irradiation. The light absorption spectrum of Bi4 NbO8 Br is wider than that of BiOBr. It is found that such enhancements give rise to the ferroelectricity induced by the intercalated NbO6 . The internal spontaneous polarization and an internal electric field formed in Bi4 NbO8 Br result in a significant band bending in its electronic structure and greatly promote the migration and separation of charge carriers in visible light irradiation. Abstract : Herein, the intercalation of NbO6 octahedral into BiOBr‐layered materials by a melting method to make Bi4 NbO8 Br nanosheets is proposed. Through theory and experiments, it is proven that the polarization can facilitate the separation and migration efficiency of photogenerated carriers and ultimately improve the photocatalytic activity of Bi4 NbO8 Br to decompose water.